An unusual respiratory tract foreign body: A case report of pediatric broncholithiasis. (September 2016) - Feng, Shuang; Liu, Dabo; Huang, Zhenyun; Zhong, Jianwen; Zhong, Jie
Abstract: Tracheobronchial foreign body aspiration is one of the most life-threatening diseases in children. Its symptom is non-specific sometimes; therefore the distinction with some similar clinical presentation pulmonary disease should be performed. Here, we reported a 5-year-old girl who was misdiagnosed with foreign body aspiration twice based on the broncho-obstructive symptom and radiologic finding. Finally, the diagnosis of broncholithiasis was confirmed by finding broncholiths in the respiratory tract through bronchoscopy. It is replied that bronchoscopy should be performed in the children with unexplained airway obstruction symptom. Furthermore, it is the first report about the broncholiths located at the upper main trachea.